2021
DOI: 10.1097/01.asw.0000722760.27083.3c
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical Site Infection after Minor Dermatologic Surgery

Abstract: BACKGROUND Surgical site infection (SSI) after dermatologic surgery is associated with poor outcomes including increased recovery time, poor cosmesis, and repeat visits to doctors. Prophylactic antibiotics are prescribed to reduce these adverse outcomes. Identifying risk factors for SSI will facilitate judicious antibiotic prophylaxis. OBJECTIVE To identify risk factors for SSI after minor dermatologic surgery. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A recent study meta-analyzed data of 4 randomized controlled trials (RCTs). 9 The included trials assessed the impact of wound covering, different topical antiseptic agents, or the use of nonsterile gloves. In line with the study findings, the authors found that advanced techniques were associated with a higher SSI risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study meta-analyzed data of 4 randomized controlled trials (RCTs). 9 The included trials assessed the impact of wound covering, different topical antiseptic agents, or the use of nonsterile gloves. In line with the study findings, the authors found that advanced techniques were associated with a higher SSI risk.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, other articles narratively summarized the literature on risk factors of SSI in skin surgery. 8,9 In addition to systematically reviewing the current literature, the authors aimed to perform meta-analysis to statistically analyze the impact of potential risk factors. Given the amount of identified relevant data, the authors categorized risk factors into patientrelated, procedure-related, and body site-related.…”
mentioning
confidence: 99%
“…5,7,9 The only statistically significant risk factor for infection in multivariable analysis was procedure location on the leg or arm; these sites were similarly identified as risk factors in a recent study of the infection rate after cutaneous excisions. 10 Further studies are warranted to determine whether alterations in perioperative protocols (technique and agent chosen for operative site preparation, topical agent applied to the site postoperatively, and utilization of postoperative compression on the legs) can improve the infection rate on the extremities.…”
Section: Discussionmentioning
confidence: 99%